Jurisdição constitucional e legitimidade: limites e possibilidades do novo desenho institucional do Tribunal Constitucional Plurinacional da Bolívia como proposta de legitimação democrática, independência e fortalecimento das instituições judiciais - Macedo, Tatiane Alves (Universidade do Vale do Rio dos Sinos, 2024)
The present research focuses on Public Law concentration area and it’s take place on the Hermeneutics, Constitution, and Right’s realization research line based on the Graduate Program in Law at the University of Vale do Rio dos Sinos. The thesis aims to analyze the democratic legitimacy of constitutional jurisdiction. To get the objectives, the first part of the work examines the emergence and evolution of constitutional justice systems, presenting the fundamental characteristics of classical systems, as well as historically addressing the expansion, reception, and hybridization of constitutional justice in the Latin American context, with emphasis on the models adopted by Brazil and Bolivia. The second part analyzes the organization model, selection process, composition, functioning, attributions, and forms of constitutional control at Bolivia’s constitutional jurisdiction. Based on the models adopted by Brazil and Bolivia, we analyze the transparency extension in the selection process, expansion of participation mechanisms, and guarantee of plurality reflect recognition of the democratic legitimacy of Constitutional Jurisdiction. The concept of legitimacy is reconstructed with Max Weber's and Pierre Bourdieu's sociology as theoretical reference. The fundamental problem that drove the research focuses on the following questions: a) What is the effectiveness of the institutional model designed for the Constitutional Court of Bolivia in guaranteeing the independence of the Judiciary? How can the experience of judicial elections in Bolivia contribute to thinking about constitutionalism in Latin America? Does the creation of a system concerned about the organization and composition of the Judiciary based on the principles of transparency and plurality make the courts more legitimate from a democratic perspective? Regarding the method of approach, Hans-Georg Gadamer’s philosophical hermeneutics is adopted. As procedural methods, Max Weber's historical-comparative and sociological methods are applied to do the analysis and understanding institutional functioning. Thus, based on the research results, own contribution is presented, pointing out paths for strengthening the democratic legitimacy of constitutional justice in Brazil.
Keywords: Jurisdição constitucional; América Latina; Modelo; Legitimidade; Tribunal Constitucional Plurinacional; Supremo Tribunal Federal; Constitutional jurisdiction; Latin American Model; Legitimacy; Plurinational Constitutional Court; Supreme Federal Court; ACCNPQ::Ciências Sociais Aplicadas::Direito